Act Your (Old) Age: Prescriptive, Ageist Biases Over Succession, Consumption, and Identity - North, Michael S. (Pers Soc Psychol Bull, 2013)
Perspectives on ageism have focused on descriptive stereotypes concerning what older people allegedly are. By contrast, we introduce prescriptive stereotypes that attempt to control how older people should be: encouraging active Succession of envied resources, preventing passive Consumption of shared resources, and avoidance of symbolic, ingroup identity resources. Six studies test these domains, utilizing vignette experiments and simulated behavioral interactions. Across studies, younger (compared with middle-aged and older) raters most resented elder violators of prescriptive stereotypes. Moreover, these younger participants were most polarized toward older targets (compared with middle-aged and younger analogues) – rewarding elders most for prescription adherences and punishing them most for violations. Taken together, these findings offer a novel approach to ageist prescriptions, which disproportionately target older people, are most endorsed by younger people, and suggest how elders shift from receiving the default prejudice of pity to either prescriptive resentment or reward.